Mirroring the Ecological Impact of Apiculture as an Indigenous Activity in Mayo Darle, Cameroon - Neba, William Shu; Shillie, Peter Ngek; Sevidzem, Ernestine Leikeki; Tanga, Pius, Tangwe (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
Although beekeeping significantly affects the environment, this agricultural sector faces numerous obstacles. This study examines the ecological impacts of local beekeeping methods in Mayo Darle, Cameroon. Employing the explanatory sequential design, 175 participants were chosen through stratified random sampling and were given structured questionnaires, interviews, and observations for gathering data. Data analysis was conducted using the Chi-Square distribution test and frequency tables. Tree planting activities (63.8%, X2 = 187.434, p = 0.000), the creation of home gardens (66%, X2 = 215.959, p = 0.000), flower pollination (45.6%, X2 = 84.291, p = 0.000), and the occurrences of bush fires (noted by 87.1% prior and 12.4% currently with beekeeping, X2 = 171.516, p = 0.000) were all reported to have shown a positive and significant increase. On the downside, it was observed that access to land had significantly diminished (reported at 98.4% before and now 0% with beekeeping, X2 = 286.803, p = 0.000), and the occurrence of medicinal plants had notably reduced (from 93.6% previously to about 14% with beekeeping, X2 = 182.778, p = 0.000). Promoting environmental sustainability via sustainable beekeeping can aid in safeguarding the ecosystem and yield beneficial ecological outcomes, mitigating the adverse impacts of climate change.